2021
DOI: 10.1097/mcg.0000000000001596
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Night-time Emergency Department Presentation on Upper Gastrointestinal Hemorrhage Outcomes

Abstract: Goals:The aim was to investigate the impact of night-time emergency department (ED) presentation on outcomes of patients admitted for acute upper gastrointestinal hemorrhage (UGIH). Background:The relationship between time of ED presentation and outcomes of gastrointestinal hemorrhage is unclear. Study:Using the 2016 and 2017 Florida State Inpatient Databases which provide times of ED arrival, we identified and categorized adults hospitalized for UGIH to daytime (07:00 to 18:59 h) and night-time (19:00 to 06:5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Night shifts in EDs are associated with poorer outcomes [33][34][35]. Here, we showed that patient arrival in the evening and especially during night shifts were highly predictive…”
Section: Discussionmentioning
confidence: 64%
“…Night shifts in EDs are associated with poorer outcomes [33][34][35]. Here, we showed that patient arrival in the evening and especially during night shifts were highly predictive…”
Section: Discussionmentioning
confidence: 64%